1987
DOI: 10.1111/j.1574-6968.1987.tb02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature limitation of hydrogen turnover and methanogenesis in anoxic paddy soil

Abstract: The shift of incubation temperature in anoxic paddy soil from 30°C to 15°C resulted in a reversible decrease of the methane production rate and of the H2 steady state partial pressure. Only at 30°C but not at 17°C, total CH4 production rates were enhanced by the addition of H2, acetate, or cellulose compared to the control. Apparent activation energies which were calculated from the temperature dependence of CH4 production were higher in presence than in absence of excess H2. Decrease of temperature caused a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
97
1
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(109 citation statements)
references
References 25 publications
9
97
1
2
Order By: Relevance
“…The temperature dependency of methane production and emission was previously described by the Arrhenius function or its logarithmic form (Conrad et al, 1987;Schütz et al, 1990;Daulat and Clymo, 1998;Kim et al, 1998):…”
Section: Modelling Of Emissionsmentioning
confidence: 99%
“…The temperature dependency of methane production and emission was previously described by the Arrhenius function or its logarithmic form (Conrad et al, 1987;Schütz et al, 1990;Daulat and Clymo, 1998;Kim et al, 1998):…”
Section: Modelling Of Emissionsmentioning
confidence: 99%
“…Microcosms of rice paddy soil were prepared from air-dried soil sampled in rice fields at the Italian Rice Research Institute in Vercelli in 1991 (Conrad et al, 1987). The soil properties were described earlier (Schtitz et al, 1989).…”
Section: Methane Measurements In Soilmentioning
confidence: 99%
“…Most studies indeed have found a slightly higher contribution of acetate, suggesting that homoacetogenesis is involved in the fermentation of the saccharides (12,51,73). It is also assumed that the fraction of hydrogenotrophic methanogenesis decreases at low temperature, as the pathway of carbon and electron flow changes, when the temperature of the rice field soil (4,16,18), as well as of the lake sediment (56,57), is shifted. Several authors demonstrated the existence of psychrotolerant homoacetogens which compete with methanogens for H 2 at low temperatures (17,33,34,45).…”
mentioning
confidence: 99%
“…From these factors temperature is recognized as one of the most important (31, 53, 58). Temperature not only has an effect on the methane production itself but also has an effect on the decomposition of organic materials from which the methanogenic substrates are produced (4,16,32,58,68).…”
mentioning
confidence: 99%
See 1 more Smart Citation